Digital Technology and CSR Disclosure on Firm Value Moderated by Financial Flexibility and Firm Size - Wahyuni, Maulana Fitri Agustustin Nur; Saraswati, Erwin; Prastiwi, Arum (University of Merdeka Malang, 2023)
This study aimed to examine the effect of digital technology and corporate social responsibility (CSR) disclosure on firm value moderated by financial flexibility and firm size. The data collected qualitatively from company websites were analyzed using quantitative content analysis. The moderating impact of financial flexibility and firm size was tested using the Moderating Regression Analysis (MRA) model. Moreover, a criteria-based method was employed to determine samples comprising 135 banking companies listed on the Indonesia Stock Exchange for 2019-2021. The results showed that digital technology and CSR disclosure positively affect firm value. This means the company website information demonstrates to stakeholders that management has optimized resources, implemented innovative models, and increased business efficiency, quality, and consistency. Therefore, it provides a good reputation to investors and potential investors. Other findings showed that financial flexibility and firm size moderate the relationship between CSR disclosure and firm value. The two variables also strengthen the relationship between CSR disclosure and firm value. However, firm size weakens the effect of digital technology disclosure on firm value. Financial flexibility does not moderate the effect of digital technology disclosure on firm value. This study has implications for the management to focus on information quality and quantity in digital technology and CSR in fulfilling the stakeholders’ decision-making needs. http://doi.org/10.26905/jkdp.v27i3.1065 .